(untitled) (Revista de História Regional, 2007)
This study tries to identify and analyze the different dimensions of the urban verticalization process, based on a case study from the middle-sized town of Ponta Grossa in Paraná, Brazil. The historical dimension is presented through the description of the temporal evolution process of the city where the verticalization process has rapidly transformed the urban landscape, resulting in an increasing loss of the urban memory, which was linked to the buildings of traditional styles. The analysis of the spatial dimension investigates the distribution of vertical constructions in the city. In general, the concentration of vertical constructions was first observed in the central area of the city and, recently, spread out to the periphery in a deconcentrated-concentrated form. The social dimension shows a high grade of social diversity among vertical constructions. A continuous substitution of social classes can be observed in these buildings, as they are apt to downgrading through material degradation. The symbolic dimension reveals how modernity, materialized by vertical constructions, can debilitate traditional local identities through the transfer of lifestyles from metropolitan cities to middle-sized towns. The economic dimension investigates the role of producers and consumers of the urban verticalized space. In this context an increasing diversification of these agents can be observed. The dimension of urban planning refers to the urban legislation framework and the control mechanism of the verticalization process in the city. The legislation is the result of demands of the dominant class and it is common that the real estate market seeks support from unspecified or incomplete legislation tools.